A new magneto-acousto-electrical detection method for defects in high conductivity non-ferromagnetic materials. (27th October 2022) - Yan, Xiaoheng; Xu, Chuwen; Lv, Jingxiang; Yang, Yanju
Abstract: In order to further enrich the non-destructive detection methods for defects in high conductivity non-ferromagnetic materials, a new method of magneto-acousto-electrical (MAE) defect detection is proposed. First, a mathematical model of MAE multi-physical field coupling with coil induction was established. Subsequently, a geometric model of the object to be tested was constructed, and the simulation software COMSOL was used to solve the physical process of MAE defect detection. Two-dimensional distributions of mass point vibration velocity, current density of the coil's cross-section, and one-dimensional curves of material vibration velocity surface integral, local current, and induced voltage as a function of time were obtained for various defect widths, defect shapes, and materials. The simulation result shows that the induction coil voltage pulse contains abundant information about the defect boundary information and the detection accuracy reaches 0.1 mm. Finally, experiments on MAE defect detection were conducted to prove the feasibility of the method. The research demonstrates a reliable method for the detection of internal defects in non-ferromagnetic materials with high electrical conductivity, such as aerospace and railways.